2007
DOI: 10.1007/s10832-007-9228-x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of hafnium oxide thin films by sol–gel method

Abstract: Hafnium oxide (HfO 2 ) films were grown on SiO 2 /Si substrates by a sol-gel method, and their crystalline structure, microstructure and electrical properties were investigated. X-ray diffraction analysis indicated that the monoclinic HfO 2 films could be obtained by annealing at 500°C. A transmission electron microscopy (TEM) image showed that the films were grown as a spherulite grain structure with a mean grain size of approximately 15 nm. The dielectric constant of the HfO 2 films of 300 nm was approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 15 publications
4
13
0
Order By: Relevance
“…Figure 7 also shows how pure PVP has a low k while increasing the nanoparticles embedded into the polymer matrix results in an increase to a high k. The dielectric property of material with nanoparticles depends on their ratio content of hafnium. The k value for our hybrid films is close to the HfO 2 reported by physical and chemical methods around 21 to 23 [4,14]; however, further studies are necessary to reach its maximum dielectric constant of the hafnium oxide. Figure 8 shows the leakage current density (J) as a function of the applied electric field (E) for our film that presented the highest k value (hybrid 2).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Figure 7 also shows how pure PVP has a low k while increasing the nanoparticles embedded into the polymer matrix results in an increase to a high k. The dielectric property of material with nanoparticles depends on their ratio content of hafnium. The k value for our hybrid films is close to the HfO 2 reported by physical and chemical methods around 21 to 23 [4,14]; however, further studies are necessary to reach its maximum dielectric constant of the hafnium oxide. Figure 8 shows the leakage current density (J) as a function of the applied electric field (E) for our film that presented the highest k value (hybrid 2).…”
Section: Resultssupporting
confidence: 77%
“…In ref. 4, the authors reported the use of sol-gel process for obtaining HfO 2 thin films with high k = 21.6, but the processing required an annealing at 750°C. For flexible electronics using plastic substrates, solution processable gate dielectrics are preferred because they are easily formed using low-temperature processing, large area applications, compatibility with light weight, and mechanically flexible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HfO 2 thin films can be grown using a wide range of vacuum based deposition techniques namely the atomic layer deposition (ALD), chemical vapor deposition (CVD), magnetron sputtering, pulsed laser deposition (PLD) and molecular beam epitaxy (MBE) . HfO 2 films deposition from solutions have also been reported . However the preferred industrial scale methods are CVD and ALD.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with organic and polymer dielectric materials, the inorganic dielectrics such as aluminum oxide (AlO x ) [1,2], zirconium oxide (ZrO x ) [3][4][5], yttrium oxide (YO x ) [6][7][8], and hafnium oxide (HfO x ) [9][10][11], are proved to be more suitable for low-operating voltage thin-film transistors (TFTs) because of their large conduction band offset and excellent solvent resistance. Among these high-k dielectrics, HfO x is considered as the most promising candidate due to its high dielectric constant (k~25-30) and wide band gap (5.68 eV) with a large conduction band (CB) offset of 1.4 eV [12,13]. The CB offset is one of the key criteria in the selection of a gate dielectric.…”
Section: Introductionmentioning
confidence: 99%